FEELINGS OF WOMEN WITH BREAST CÂNCER - Guilherme Pereira, Victor; Cristina Condé, Renata; da Silva Alves, Renato; Cristina Santos Alves, Elaine; Souza França Ramos, Robson; Esméria Neta, Maria; do Carmo Ferreira Costa Cordeiro, Maria; de Cássia Caldeira Santos Goes, Rita; Scremin, Marlete; Batista Vieira, Isabella; Theresa Faria de Almeida, Anna; Pereira Amancio, Janaina; et al. (Health and Society, 2024)
Objective: to know the feelings of women diagnosed with breast cancer. Materials and Methods: The theme was addressed through an integrative literature review, an instrument of Evidence-Based Practice (EBE). A survey was carried out in the BDENF, LILACS and SciELO databases from August to September 2023. The following descriptors were used: Feelings. Breast cancer. Diagnosis, they were combined for search. Publications in the study were published Portuguese that made the abstract available in their databases. Results: We started from the systematization of categories of analysis that represent the axis around which the product of the dynamics performed is articulated, namely: Feelings experienced by women in the face of breast cancer and Family support for women with breast cancer. Final Considerations: Feelings arising from breast cancer diagnosis translate into fear, anxiety, uncertainty, hopelessness and anger.